PENGARUH VARIABEL MAKROEKONOMI DAN MIKROEKONOMI TERHADAP RETURN DEFENSIVE STOCKS YANG TERDAFTAR PADA JAKARTA ISLAMIC INDEX (JII) PERIODE 2014-2018 - Irfan, Mohammad Syihabul (Jurnal Ilmiah Mahasiswa FEB, 2020)
The Islamic capital market is believed to be able to withstand the crisis compared to conventional capital markets. Investors invest the excess funds into the Islamic capital market with the aim of expecting a return. Returns that will be obtained by investors are influenced by macroeconomic conditions which include inflation, economic growth, Indonesian sharia bank certificates, sukuk. The microeconomic factors are influenced by earnings per share and debt equity ratio. The method used in this study is panel data regression using random effect models. The results obtained in this study indicate that the variables inflation, economic growth and Bank Indonesia Sharia Certificates (SBIS) have no significant effect. As for the sukuk variable, earnings per share (EPS) and debt equity ratio (DER) significantly influence stock returns. Keywords: Inflation, Economic Growth, SBIS, Sukuk, EPS, DER, Stock returns, Defensive stocks.